Microscopic and dielectric analyses of vanadium and tungsten modified barium zirconium titanate ceramics - Moura, Francisco; Simões, Alexandre Zirpoli; Zaghete, Maria Aparecida [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (American Scientific Publishers, 2010)
Dielectric spectroscopy was used in this study to examine polycrystalline vanadium and tungstendoped BaZr 0.1Ti 0.90O 3 (BZT10:2V and BZT10:2W) ceramics obtained by the mixed oxide method. According to X-ray diffraction analyses, addition of vanadium and tungsten lead to ceramics free of secondary phases. SEM analyses reveal that both dopants result in slower oxygen ion motion and consequently lower grain growth rate. Temperature dependence dielectric study showed normal ferroelectric to paraelectric transition well above the room temperature for the BZT10 and BZT10:2V ceramics. However, BZT10:2W ceramic showed a relaxor-like behavior near phase transition characterized by the empirical parameter γ. Piezoelectric force microscopy images reveals that the piezoelectric coefficient is strongly influenced by type of donor dopant suggesting promising applications for dynamic random access memories and data-storage media. Copyright © 2010 American Scientific Publishers All rights reserved.
Keywords: Ceramics; Dieletric response; Dopants; Mixed oxide; Piezoelectricity; Dielectric analysis; Dielectric studies; Donor dopants; Dynamic random access memory; Empirical parameters; Ion motions; Mixed oxide method; Paraelectric transitions; Piezoelectric coefficient; Piezoelectric force microscopy; Polycrystalline; Room temperature; Secondary phasis; SEM analysis; Temperature dependence; Zirconium titanate; Barium; Crystallography; Digital storage; Doping (additives); Ferroelectric ceramics; Grain growth; Tungsten; Vanadium; X ray diffraction; X ray diffraction analysis; Zirconium; Ceramic materials